Source/Drain Materials for Ge nMOS Devices: Phosphorus Activation in Epitaxial Si, Ge, Ge1−xSnx and SiyGe1−x−ySnx. (7th May 2020) - Vohra, Anurag; Makkonen, Ilja; Pourtois, Geoffrey; Slotte, Jonatan; Porret, Clement; Rosseel, Erik; Khanam, Afrina; Tirrito, Matteo; Douhard, Bastien; Loo, Roger; Vandervorst, Wilfried
Abstract : This paper benchmarks various epitaxial growth schemes based on n -type group-IV materials as viable source/drain candidates for Ge nMOS devices. Si:P grown at low temperature on Ge, gives an active carrier concentration as high as 3.5 × 10 20 cm −3 and a contact resistivity down to 7.5 × 10 −9 Ω.cm 2 . However, Si:P growth is highly defective due to large lattice mismatch between Si and Ge. Within the material stacks assessed, one option for Ge nMOS source/drain stressors would be to stack Si:P, deposited at contact level, on top of a selectively grown n -Si y Ge1− x − y Sn x at source/drain level, in line with the concept of Si passivation of n -Ge surfaces to achieve low contact resistivities as reported in literature (Martens et al. 2011 Appl. Phys. Lett., 98, 013 504). The saturation in active carrier concentration with increasing P (or As)-doping is the major bottleneck in achieving low contact resistivities for as-grown Ge or Si y Ge1− x − y Sn x . We focus on understanding various dopant deactivation mechanisms in P-doped Ge and Ge1− x Sn x alloys. First principles simulation results suggest that P deactivation in Ge and Ge1− x Sn x can be explained both by P-clustering and donor-vacancy complexes. Positron annihilation spectroscopy analysis, suggests that dopant deactivation in P-doped Ge and Ge1− x Sn x is primarily due to the formation of P n -V and Sn m P n -V clusters.